Pemakaian Produk Fast Fashion sebagai Bentuk Citra Diri Generasi Z: Studi Fenomenologi terhadap Citra Diri Generasi Z - Ayudhia Putri Farhani; Oji Kurniadi (UNISBA Press, 2022)
Abstract. The use of fast fashion products is common among generation Z because it is felt to be part of their efforts to form a self-image and look